(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This study examines successful methodologies for instructing English to learners with impairments, emphasizing inclusive education, adaptive teaching tactics, and technological interventions. The study emphasizes individualized instruction, multimodal learning, and assistive technology as essential strategies for enhancing language acquisition among students with diverse disabilities. Research indicates that a learner-centered methodology improves engagement and understanding.